2007
DOI: 10.1093/aob/mcm147
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variability in Nodulation and Root Growth Affects Nitrogen Fixation and Accumulation in Pea

Abstract: The hypernodulating mutants did not accumulate more nitrogen, probably due to the C cost for nodulation being higher than for root development. Enhancing exogenous nitrogen supply at the end of the growth cycle, by increasing the potential for root N uptake from soil, seems a good option for improving pea seed filling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
48
1
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(62 citation statements)
references
References 37 publications
10
48
1
1
Order By: Relevance
“…Previous study has shown that the choice of pea cultivar is of great importance, as the variation of protein content depends on the genetic information encoded in the plant (Bourion et al, 2007). This type of variation can be also observed in the current study, when under the same conditions and treatments, differences in protein content are due to the pea cultivar ( Figure 2, Figure 3).…”
Section: Protein Content In Peassupporting
confidence: 81%
See 1 more Smart Citation
“…Previous study has shown that the choice of pea cultivar is of great importance, as the variation of protein content depends on the genetic information encoded in the plant (Bourion et al, 2007). This type of variation can be also observed in the current study, when under the same conditions and treatments, differences in protein content are due to the pea cultivar ( Figure 2, Figure 3).…”
Section: Protein Content In Peassupporting
confidence: 81%
“…Increased protein content can be achieved by using nitrogen fertilizers or through seed inoculation with the appropriate strains of rhizobia (Ahmed, It has been suggested that legume yield and and the protein content stored in legume seeds increase depending on the genotype of Rhizobium sp. strain used for inoculation (Ahmed et al, 2007;Bourion et al, 2007;Saleh, Zaman, & Kabir, 2013). Commercial rhizobium inoculants are available, specially selected to match the specific species to reach the optimal nitrogen fixation activity (Lindström et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Instead, hypernodulation most often limited plant growth and productivity (Sagan et al 1993;Bhatia et al 2001;Novak 2010;Voisin et al 2013). Hence, most studies on hypernodulating mutants have reported negative pleiotropic traits related to carbon nutrition such as depressed shoot growth, shortened internodes or fasciation of the stem, and reduction of roots development and growth (e.g., pea : Postma et al 1988;Duc and Messager 1989;Sagan and Duc 1996;Krusell et al 2002;Bourion et al 2007; soybean: Matsunami et al 2004;Voisin et al 2013). These pleiotropic effects might be a direct effect of the mutated gene on those carbon nutrition traits, or it may result from a physiological consequence of deregulated (and therefore excessive) nodule number (Novak et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Among them, three lines differing in the genetic basis of hypernodulation were selected, namely mutants of the SYM28, SYM29, and NOD3 genes (Sagan and Duc 1996;Postma et al 1988;Krusell et al 2002). Among diverse mutants of each gene, we first selected the allele displaying the weakest hypernodulating phenotype, i.e., which displayed the least depressed shoot growth compared to the parental line (i.e., P64, P118, and P121 mutants for the SYM28, SYM29, and NOD3 genes, respectively; Bourion et al 2007). In the 2009 experiment, wild type Frisson was grown together with an allelic series of the seven hypernodulating mutants of SYM29 (P118, P87, P90, P89, P91, P93, and P122), each differing in sequence of the sym29 allele (Krusell et al 2002) and varying in hypernodulating intensity, as described in Voisin et al 2013.…”
Section: Introductionmentioning
confidence: 99%
“…Although the nature of the signals involved in the AON regulation has not been unambiguously elucidated, potential candidate compounds include either phytohormones, like ethylene (Schmidt et al, 1999), auxin (van Noorden et al, 2006) or brassinosteroids, jasmonic and abscisic acids (Oka-kira & Kawaguchi, 2006), or long distance signals involving the whole plant N status (Ruffel et al, 2008). Hypernodulating mutants, which are defective in AON, display excessive nodule numbers compared to wild type (Bourion et al, 2007) and maintain nodulation even when roots are exposed to nitrate. It was observed in pea that nodule number can vary in a wide range for a given wild type genotype, not only depending on nitrate but also on light conditions (Voisin et al, 2010).…”
Section: Adaptative Response To N Limitationmentioning
confidence: 99%